Analysis Vision Education in Election President 2024 in Indonesia: Urgency, Relevance And Opportunity Implementation from Partner Presidential and Vice Presidential Candidates Number Sequence 01 - Nanda Rahayu Agustia; Muhammad Sirozi; Sholihah Titin Sumarti (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this article is to explain dynamics of Indonesian politics, the 2024 presidential election (Pilpres) offers a stage for presidential and vice presidential candidates to present their educational vision to the public. This study focuses on an in-depth analysis of the urgency, relevance and opportunities for implementing the educational vision proposed by the presidential and vice presidential candidate pair number 01. Through a qualitative approach, this research describes how this educational vision can respond to contemporary challenges in the education sector, synchronizing with socio-economic needs of society, and the potential for their realization within the existing public policy framework. The analysis found that the educational vision of the 01 presidential and vice presidential candidates has high urgency in overcoming disparities in access to education, improving the quality of learning, and integrating technology in education. This vision is relevant to the need to develop Indonesian human resources that are globally competitive and adaptive to changing times. Implementation opportunities, meanwhile, are analyzed through the lens of resource availability, regulatory framework, and existing political and social support. This study proposes several strategic recommendations to maximize the potential for implementing this educational vision, including increasing collaboration between sectors, strengthening evidence-based education policies, and utilizing educational technology.